2018
DOI: 10.21315/mjms2018.25.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Living and Coping with Suicidal Ideation among Adolescents in Malaysia

Abstract: IntroductionThe rate of suicide ideation everywhere continues to increase, and adolescents are therefore at risk of displaying suicidal behaviour. This study examined the protective role of the reasons for living and coping strategies in reducing suicidal ideation among young adolescents in Malaysia.MethodsA cross-sectional survey was conducted among 176 adolescents aged between 13 and 19 years of age with the majority being Malay and Muslim. The Brief Reasons for Living for Adolescents (BRFL-A), Jalowiec Copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…However, parents or Guardian, family, relatives, friends, neighbours, and the society are not to be spared. The study by Che, Ibrahim, Amit, Abdul-Kadir, Halim, et al, (2018), examined suicidal intention among young adolescents in Malaysia in which the results showed that the reasons for living and palliative coping strategy correlated negatively with suicidal intention while multiple regressions revealed that family alliance and optimistic and palliative coping strategies were found to be significant reasons for living that protect adolescents from suicidal thoughts. Furthermore, this means that families contribute to suicide through their contribution to the level of stress experienced by the adolescent and their failure to provide social support.…”
Section: Socioeconomic Class Of My Familymentioning
confidence: 99%
“…However, parents or Guardian, family, relatives, friends, neighbours, and the society are not to be spared. The study by Che, Ibrahim, Amit, Abdul-Kadir, Halim, et al, (2018), examined suicidal intention among young adolescents in Malaysia in which the results showed that the reasons for living and palliative coping strategy correlated negatively with suicidal intention while multiple regressions revealed that family alliance and optimistic and palliative coping strategies were found to be significant reasons for living that protect adolescents from suicidal thoughts. Furthermore, this means that families contribute to suicide through their contribution to the level of stress experienced by the adolescent and their failure to provide social support.…”
Section: Socioeconomic Class Of My Familymentioning
confidence: 99%
“… 8 , 9 These protective factors could differ between ethnicities and cultures, underscoring the crucial role of cultural and social values in protecting youth against suicidal behavior. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Whilst suicide risk and ideation are often associated with specific traumas, depression, and substance abuse, [7][8][9] a suicidal process may, however, take weeks to years for the fatal transition to occur from suicidal ideation and attempts to dying by suicide. 10 From the community surveys that were conducted in 21 countries (n >100 000 individuals), the World Health Organization found that the 12-month prevalence of suicidal ideation was approximately 2%, 11 a lifetime prevalence of 9%, 12 and 33 and 30% of those who had suicidal ideation progressed to suicide planning and attempt, respectively. 13 Among university students, the lifetime prevalence of suicidal ideation and suicide attempt was 22.3% and 3.2% respectively.…”
Section: Introductionmentioning
confidence: 99%